2002
DOI: 10.1126/science.1069878
|View full text |Cite
|
Sign up to set email alerts
|

African Pastoralism: Genetic Imprints of Origins and Migrations

Abstract: The genetic history of African cattle pastoralism is controversial and poorly understood. We reveal the genetic signatures of its origins, secondary movements, and differentiation through the study of 15 microsatellite loci in 50 indigenous cattle breeds spanning the present cattle distribution in Africa. The earliest cattle originated within the African continent, but Near East and European genetic influences are also identified. The initial expansion of African Bos taurus was likely from a single region of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
456
0
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 469 publications
(517 citation statements)
references
References 10 publications
55
456
0
6
Order By: Relevance
“…They are further described in Table II and [4,9,10,18,23]. To avoid confusion and mingling of breeds or strains having the same name, it is assumed that the country of conservation is equal to the origin of the blood sample (Tab.…”
Section: Breedsmentioning
confidence: 99%
“…They are further described in Table II and [4,9,10,18,23]. To avoid confusion and mingling of breeds or strains having the same name, it is assumed that the country of conservation is equal to the origin of the blood sample (Tab.…”
Section: Breedsmentioning
confidence: 99%
“…They are also thought to have interbred with the Lateralhorned Zebus to produce the various Sanga cattle, which later migrated south of the Sahara towards the Great Lakes and beyond [15,21]. Previous studies by Freeman et al [9] and by Hanotte et al [14] have indicated minimal recent male-mediated indicine gene introgression into the Ankole cattle populations, either through the Zenga or Bos indicus populations.…”
Section: Introductionmentioning
confidence: 99%
“…Ordination summarises all the variation in the study area and accommodates each population as a study unit (Manel et al 2003). Then, the inverse distance weighted interpolation of the major principal components leads to a synthesis map, which gives insights into the spatial pattern concerned (Hanotte et al 2002). AFC analyses were performed using GENETIX and interpolation using GRASS GIS software (GRASS Development Team 2008).…”
Section: Population Structure Analysismentioning
confidence: 99%